The impact of organizational justice on employee innovative work behavior: Mediating role of knowledge sharing - Tayyaba Akram; Shen Lei; Muhammad Jamal Haider; Syed Talib Hussain (Journal of Innovation & Knowledge (JIK), 2020)
This study attempts to find out the impact of organizational justice on the innovative work behavior of employees working in Chinese telecommunication sector, while analyzing the mediating role of knowledge sharing between the independent and dependent variables of this study. In order to test the study hypotheses, a data of 345 respondents working in Chinese telecommunication industry was collected. Confirmatory factor analysis suggested a good model fit, while structural equation model provided significant and positive effect of organizational justice on the employee innovative work behavior and knowledge sharing. Knowledge sharing mediated the relationship between organizational justice and employee innovative work behavior. Managerial and practical implications of the study are also provided.
Keywords: 650; Organizational justice; Knowledge sharing; Employee innovative work behavior; China